2022
DOI: 10.1097/sap.0000000000003166
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Application of 3-Dimensional Printing Models in Orbital Blowout Fractures—A Preliminary Study

Abstract: Background: Application of 3-dimensional (3D) printing technology has grown in the medical field over the past 2 decades. In managing orbital blowout fractures, 3D printed models can be used as intraoperative navigators and could shorten the operational time by facilitating prebending or shaping of the mesh preoperatively. However, a comparison of the accuracy of computed tomography (CT) images and printed 3D models is lacking. Material and Methods: This is a single-center retrospective study. Patients with un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Recently, 3DPT has been increasingly employed to support orbital fracture repair surgeries. Studies have demonstrated that 3DPT can enhance the precision of orbital fracture repair surgeries [22] . This study's strength lies in investigating the impact of combined assistive technologies, including surgical navigation, endoscopy, and 3D printing, on the surgical outcomes of OBF.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, 3DPT has been increasingly employed to support orbital fracture repair surgeries. Studies have demonstrated that 3DPT can enhance the precision of orbital fracture repair surgeries [22] . This study's strength lies in investigating the impact of combined assistive technologies, including surgical navigation, endoscopy, and 3D printing, on the surgical outcomes of OBF.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the accuracy of the 3D models and two-dimensional CT images was compared and found to have a difference of < 1 mm that was not statistically significant. 19 The accuracy of these models translates into fewer postoperative complications. Other advantages to custom 3D-printed implants are shortened intraoperative times, reduced length of anesthesia, and greater precision in restoration of orbital volume to match the unaffected orbit.…”
Section: Overview Of the Traditional Approach To Acute Orbital Traumamentioning
confidence: 99%